Performance of CPT-based methods to assess monopile driveability in North Sea sands - Byrne, T.; Gavin, K.; Prendergast, L.J.; Cachim, P.; Doherty, P.; Chenicheri Pulukul, S. (Elsevier, 2018)
Offshore pile driving is a high-risk activity as delays can be financially punitive. Experience of pile driving for offshore jacket structures where pile diameters are typically < 2 m has led to the development of empirical pile driveability models with proven predictive capability. The application of these methods to larger diameter piles is uncertain. A major component of driveability models involves estimating the static resistance to driving, SRD, a parameter analogous to pile axial capacity. Recent research on axial capacity design has led to improved models that use Cone Penetration Test, CPT data to estimate pile capacity and include for the effects of friction fatigue and soil plugging. The applicability of these methods to estimating pile driveability for larger diameter piles is of interest. In this paper, recent CPT based axial capacity approaches, modified for mobilised base resistance and ageing, are applied to estimating driveability of 4.2 m diameter piles. A database of pile installation records from North sea installations are used to benchmark the methods. Accounting for factors such as pile ageing and the relatively low displacement mobilised during individual hammer blows improves the quality of prediction of pile driveability for the conditions evaluated in this study.